2013
DOI: 10.1080/07481187.2013.766655
|View full text |Cite
|
Sign up to set email alerts
|

Are We All Equal at Death?: Death Competence in Municipal Cemetery Management

Abstract: Managers of local government cemeteries should balance social and cultural expectations with fiscal responsibility and when they do so they demonstrate death competence in cemetery management. This study reviews the cultural and social equity aspects of the consumption of cemetery services and develops tools to take into account social equity and cultural concerns for public sector cemetery managers. Cemetery demand and pricing models are developed and applied to the case of Austin, Texas. These models enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…On the one hand there is the 'commercial' focus of the private sector, and on the other the 'community service' and broader promotion of culture and community life provided by the public sector (Longoria, 2014). As one council operator reflected: "I don't think there's really scope for a private operator to come in and turn a profit, that's what they want to do, whereas we're providing a service to the community.…”
Section: Private Sector Provisionmentioning
confidence: 98%
“…On the one hand there is the 'commercial' focus of the private sector, and on the other the 'community service' and broader promotion of culture and community life provided by the public sector (Longoria, 2014). As one council operator reflected: "I don't think there's really scope for a private operator to come in and turn a profit, that's what they want to do, whereas we're providing a service to the community.…”
Section: Private Sector Provisionmentioning
confidence: 98%
“…After disasters such as Hurricanes Katrina and Rita, the need to reduce social vulnerability became clear (Gooden, Jones, Martin and Boyd ), but seemingly little has been done to correct these problems, as highlighted by early COVID‐19 data. Longoria () found that African American families in Austin, Texas, are at risk of spending between 25 and 26.8 percent of their annual income on funeral expenses, compared with 15 to 16.1 percent for white families. There is a disparity when it comes to funeral costs.…”
Section: Cemeteries In Disaster Responsementioning
confidence: 99%
“…Apart from the legal and institutional context, there is an emotional aspect of the choice of burial location. When death occurs in the country of settlement, it often triggers grappling with the question of the meaning of home and homeland, and stirs feelings of belonging (Longoria, 2014;Balkan, 2015a;Outmany, 2016). Accordingly, the act of funeral and burial is an important way of demonstrating where the deceased as well as his/her descendants belong.…”
Section: Death In a Migratory Contextmentioning
confidence: 99%
“…Studies have further suggested that by choosing the country of origin as the burial location, immigrants might also aim to strengthen the belonging of future generations to their ancestral homelands (Jonker, 1996;Hunter and Ammann, 2016). When it comes to the immigrant offspring's views regarding burial practices, however, the literature shows no consensus on the issue (Attias-Donfut and Wolff, 2005;Longoria, 2014), suggesting that as the second and subsequent generations intend to stay in the country of settlement, the question of where to be buried will remain highly pertinent (Milewski and Otto, 2016).…”
Section: Death In a Migratory Contextmentioning
confidence: 99%